PENGARUH JUMLAH DANA PIHAK KETIGA (TABUNGAN DAN DEPOSITO) DAN NON-PERFORMING LOAN (NPL) TERHADAP JUMLAH KREDIT YANG DISALURKAN PT. BANK PERKREDITAN RAKYAT JAWA TIMUR CABANG BATU - Safitri, Titi; ati, Sumi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This research aims to determine the effect of the amount of third-party funds (savings and deposito) and Non-Performing Loan (NPL) to the amount of outstanding loans Rural Bank of East Java branch of Batu. Besides that, the aims of this research is to determine which variable is the most dominant of the total outstanding loans. This research is explanatory research. The type of data used quantitative and qualitative data during the period January 2011 to December 2013. This research uses multiple regression analysis with F-test and t-test and classical assumption test. From the results of multiple regression analysis shows that the third-party funds and NPL take effect simultaneously and partially to the total outstanding loans and deposito is the most dominant variable of Rural Bank of East Java branch of Batu. Keywords:Third-party Funds, Savings, Deposito, Non-Performing Loan, Rural Bank, Rural Bank of East Java Branch of Batu